Effect of Lymph Node Clearance Modalities on Chronic Cough after Surgery in Non-small Cell Lung Cancer - Zekai ZHANG; Gaoxiang WANG; Zhengwei CHEN; Mingsheng WU; Xiao CHEN; Tian LI; Xiaohui SUN; Mingran XIE (Chinese Journal of Lung Cancer, 2025)
Background and objective Lung cancer has the highest mortality rate among all malignant tumors, and non-small cell lung cancer (NSCLC) accounts for about 80%-85% of all lung cancers. Lobectomy and lymph node dissection are one of the most important treatment methods, and lymph node dissection, as an important part, has attracted much attention. And its mode and scope of dissection may affect postoperative complications, particularly the occurrence of chronic cough. The aim of this study is to investigate the effect of lymph node dissection on postoperative chronic cough in patients with NSCLC undergoing lobectomy, and to provide clinical evidence for optimizing surgical strategy and reducing postoperative chronic cough. Methods A retrospective analysis was conducted on the clinical data of 365 NSCLC patients who underwent lobectomy at the First Affiliated Hospital of University of Science and Technology of China from December 2020 to December 2023. The relationship between clinical characteristics and postoperative chronic cough was analyzed. The Chinese version of the Leicester Cough Questionnaire (LCQ-MC) scores were collected from the patients at 2 time points: 1 day before surgery and 8 weeks after surgery. Patients were divided according to lymph node dissection methods, to explore the relationship between lymph node dissection and chronic cough after lobectomy. Additionally, patients were divided into chronic cough and non-chronic cough groups based on the presence of postoperative chronic cough, to investigate whether perioperative data, lymph node dissection methods, and lymph node dissection regions were influencing factors. Results Patients undergoing lobectomy were more likely to have chronic cough after surgery in the systematic lymph node dissection group than in the lymph node sampling group (P<0.05). LCQ-MC scale evaluation showed that the psychological, physiological, social and total score of the patients in systematic lymph node dissection group were significantly lower than those in lymph node sampling group (P<0.05). Multivariate analysis showed that anesthesia time, operation site, lymph node dissection method, whether to perform upper mediastinal lymph node dissection, number of upper mediastinal lymph node dissection, whether to perform lower mediastinal lymph node dissection and total number of lymph node dissection were independent risk factors for postoperative chronic cough in NSCLC patients (P<0.05). Conclusion When NSCLC patients underwent lobectomy, lymph node sampling was associated with a significantly lower risk of chronic cough than systematic lymph node dissection. Dissecting lymph nodes in the upper and lower mediastinal regions and the number of lymph nodes dissected may increase the risk of postoperative cough and reduce the quality of life of patients after surgery.